Determination of Land Use Effects on Flood Risk by Using Integration of GIS and Remote Sensing - (:unkn) unknown (IEEE, 2009)
The various human activities are one of the main affecting factors on natural disasters. Human effects not suitable for land use potential can cause both physical and moral damages. Yeniciftlik stream basin, located within the boundaries of Beykoz, a suburb of Istanbul in Turkey, has been selected as the study area. It covers an area of 3.66 km(2) of the Yeniciftlik River within the boundaries of the Beykoz district. Nowadays, there are many methods for flood researches. Not only new satellite technologies but also improvements of GIS provide important advantages in the researches of natural disasters. In this study, the effects of land use features on flood occurrence have been determined by using GIS and remote sensing. Pixel-based classification method has been used for analyzing land use features. IKONOS pan-sharpened satellite imagery has been used for current land use. Processes of flood analyze were performed by means of HEC-GeoRAS (ArcGIS 9.3) and HEC-RAS 4.0 (Hydrologic Engineering Centers River Analysis System) hydraulic software. In this study, geometric data composes the basis of the model. These data are rivers, river coasts, stream ways, cross sections and land use. The geometric data of the study area are produced with HEC-GeoRAS and all other data were gathered here before they were transferred to the HEC-RAS. After the input of the geometric data stream, data related to the basin where the modeling will be done were input. Hydraulic and hydrologic modeling for the flood risk studies, flood flow rates of 10, 50 and 100 years were calculated using maximum flood flow rates of 30 years, and flood risk maps were obtained making hydraulic modeling according to the data obtained.
Keywords: Remote sensing; GIS; Landuse; Flood